1998
DOI: 10.1108/01437729810220419
|View full text |Cite
|
Sign up to set email alerts
|

Non‐standard working‐time arrangements in Australia and New Zealand

Abstract: In the post-World War II period, working and social life has been organised around the concept of a standard day and week with premium payments for work undertaken during unsocial hours. In recent years, this standard model for organising working-time has been placed under pressure from a range of supplyand demand-side factors. This paper reports on the findings of 1995 survey into the extent and nature of non-standard working-time arrangements in Australia and New Zealand. This paper seeks to assess whether e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 6 publications
0
15
0
1
Order By: Relevance
“…In Belgium, a collective agreement and a statutory law was passed in 1987 enabling companies to introduce new work schedules that relaxed the restrictions on night-time and Sunday work. This changing legislation has frequently been implicated as the starting point for a 24-hour society and economy, in which 'round-the-clock' production and consumption are increasingly considered as normal practices (Garhammer, 1995;Allan et al, 1998;Breedveld, 1998;Masson, 1999;Golden, 2001).…”
Section: The Coming Of a 24-hour Society?mentioning
confidence: 99%
See 2 more Smart Citations
“…In Belgium, a collective agreement and a statutory law was passed in 1987 enabling companies to introduce new work schedules that relaxed the restrictions on night-time and Sunday work. This changing legislation has frequently been implicated as the starting point for a 24-hour society and economy, in which 'round-the-clock' production and consumption are increasingly considered as normal practices (Garhammer, 1995;Allan et al, 1998;Breedveld, 1998;Masson, 1999;Golden, 2001).…”
Section: The Coming Of a 24-hour Society?mentioning
confidence: 99%
“…Generally speaking, the 24-hour society is believed to be driven by exogenous or macro-level factors (Allan et al, 1998;Hamermesh, 1999;Masson, 1999;Baker et al, 2003;Presser, 2005). Flexibilization and destandardization have often been understood as ways to accommodate changes in technology and the global market (Garhammer, 1995).…”
Section: The Coming Of a 24-hour Society?mentioning
confidence: 99%
See 1 more Smart Citation
“…During both phases it has been suggested that the worker seeks improvements to family and work conditions. As penalty payments are highest at night and over the weekend (Allan et al 1998) it may be that these workers are prepared to work at any time, on any day, in order to maximize their financial remuneration and hence improve family financial conditions.…”
mentioning
confidence: 99%
“…While shift work may be broadly defined (2), work start times that fall between 04.00-08.00 hours are typically classified as early-morning shift work (3)(4)(5). Recent data indicate that a considerable proportion of employees in Western countries are engaged in early-morning shift work: over a third of the Australian workforce starts work by 07.30 hours (6), 32.7% of the Swedish work force regularly starts work between 03.00-05.30 hours (7), and about 20% of the total workforce in the USA starts work between 02.30-07.00 hours (8).…”
mentioning
confidence: 99%